Factors Influencing Organizational Performance: Work Environment, Training-Development, Management and Organizational Culture - Cera, Elona; Kusaku, Anri (European Journal of Economics and Business Studies, 2020)
Public sector performance has attracted the attention of many researchers, because it is considered as one of the key factors for efficiency and positive results in the public sector. Various studies have identified many variables that influence performance in public organizations. Four of them were considered in this study: organizational culture, work environment, training and development, and management. A sample of 162 local government employees were surveyed to carry out this research. Statictical tests such as Cronbch Alpha, KMO and Bartlett, factor analysis, correlation and regression were used to achieve the results. The study shows that variables as: work environment, training-development and management are important determinants of organizational performance. Meanwhile, organizational culture doesn’t corelate positively with organisational perfomance.